2018
DOI: 10.1200/jco.2017.77.6351
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Structure Injury After Radiotherapy for Breast Cancer: Cross-Sectional Study With Individual Patient Data

Abstract: Purpose Incidental cardiac irradiation can cause cardiac injury, but little is known about the effect of radiation on specific cardiac segments. Methods For 456 women who received breast cancer radiotherapy between 1958 and 2001 and then later experienced a major coronary event, information was obtained on the radiotherapy regimen they received and on the location of their cardiac injury. For 414 women, all with documented location of left ventricular (LV) injury, doses to five LV segments were estimated. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 31 publications
2
78
0
5
Order By: Relevance
“…Darby et al showed an increase in coronary events of 7.4% per Gy in MHD, but prediction was not improved by including LAD in the model [4]. However, in a more recent study from the same group, doses to LAD were shown to be relevant [18]. In a study using modern 3DCRT and delineating the cardiac structures, the dose to the left ventricle (LV-V5) seemed to be a better predictor for acute cardiac events than the mean heart dose [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Darby et al showed an increase in coronary events of 7.4% per Gy in MHD, but prediction was not improved by including LAD in the model [4]. However, in a more recent study from the same group, doses to LAD were shown to be relevant [18]. In a study using modern 3DCRT and delineating the cardiac structures, the dose to the left ventricle (LV-V5) seemed to be a better predictor for acute cardiac events than the mean heart dose [16].…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al have shown, using simulated heart doses and more contemporary RT, an excess of risk rate of 4.1% per Gy of the MHD [17]. A recent study from the same group showed a significant correlation between simulated doses to LAD and later stenosis [18]. The aim of the present study was to examine whether there is a relationship between radiation dose to the CAs and a later coronary stenosis at this location that requires a coronary intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have established thresholds over which the risk of RT pneumonitis and esophagitis becomes clinically significant, [10][11][12] and additional literature has described direct correlations between increasing RT dose to the heart and significant cardiac events. [13][14][15] Cardiac damage inflicted by RT can lead to a myriad of long-term complications, including but not limited to coronary artery disease progressing to ischemic events, such as myocardial infarction, and eventual congestive heart failure, as well as arrhythmias and valvular changes. 13,16 The risk of cardiac toxicity can be further heightened by anthracycline-based chemotherapy or human epidermal growth factor receptor 2 directed therapies, which are commonly used in the treatment of LABC.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Lately, detailed studies of the specific cardiac structures' absorbed radiation dose in thoracic radiation therapy 24,36,37 , and the efforts to understand the specific radiation dose-volume effects in the heart have emerged. 4,[38][39][40][41] With expanding knowledge in this field, German Society of Radiation Oncology (DEGRO) recommends new stringent dose constraints for the heart and its substructures: MWHD < 2. 5 42 To standardize the reporting of cardiac imaging regardless of diagnostic modality, both The American Society of Echocardiography and the European Association of Cardiovascular Imaging recommend using a segmentation model of the LV to assess regional LV function.…”
Section: Introductionmentioning
confidence: 99%